Evaluating Social and Clinical Value in Health Interventions: A Cross-Sectional Study of Vaccine Uptake in Low-Income Communities - Sethi, Dipak; Suvvada, Harsha Teja; Bose, Shayani; Bandyopadhyay, Sukanta (Journal of Neonatal Surgery, 2025)
Low-income populations still present with low vaccine utilization due to factors such as poor access to healthcare, low health literacy, and perceived social and clinical utility of vaccines. This research aims to identify factors that influence vaccination behaviors to understand how to enhance coverage in these regions. A self-administered questionnaire was used to evaluate the participants’ vaccination history and perception of the utility of immunization among 500 adults residing in targeted low-income communities. Descriptive and regression analyses were used to establish the predictors of vaccine uptake. Results showed an overall uptake rate of 42%, with slightly higher rates among females (45%) than males (39%). Education and income levels were important factors: participants with post-secondary education reported a 55% vaccination rate, while those above the poverty line had a 50% rate. Notably, social and clinical perceptions of the vaccine were significantly related to the uptake of the vaccine, as people with positive perceptions of vaccination health and community benefits were likely to be vaccinated. The results imply that increasing health literacy, increasing the availability of healthcare services, and raising awareness about community-based education could greatly improve the uptake of vaccines. Specifically, an intervention known as ‘client tracking and tracing’ can directly refer susceptible population groups to vaccinating facilities to increase immunity coverage among disadvantaged persons who might be discouraged from taking vaccines due to one reason or the other